Orbitotemporal Neurofibromatosis: Case Report - Mahalakshmi Balasubramanyam; Goutham Cugati; Bipasha Mukherjee (Case Reports in Ophthalmological Medicine)
Plexiform neurofibromas occur in about 60% of neurofibromatosis type 1(NF-1) patients and can lead to severe morbidity by disfigurement or compression of vital structures. Moreover, these tumors can undergo malignant transformation. Both focal and localized bone abnormalities are part of the phenotypic expression of NF-1. We report a rare case of severe cranioorbital plexiform neurofibromatosis in a young male and discuss the classification, clinical features, and various treatment options of orbit-temporal neurofibromatosis type 1.